Taxonomy and distribution of Pectinariidae (Annelida) from Iceland with a comparative analysis of uncinal morphology - Parapar, Julio; Palomanes, Verónica; Helgason, Gudmundur V.; Moreira, Juan (European Journal of Taxonomy, 2020)
Based on samples collected during the BIOICE project off Iceland, four species of marine annelids belonging to the family Pectinariidae were identified: Amphictene auricoma (O.F. Müller, 1776), Cistenides granulata (Linnaeus, 1767), Cistenides hyperborea Malmgren, 1865 and Lagis koreni Malmgren, 1866. Taxonomic remarks and data on geographical and bathymetric distribution are presented. The distribution of each species off Iceland was evaluated and two patterns were defined: C. granulata and C. hyperborea were mainly found in waters off the northeast coast, while A. auricoma and L. koreni were found on the southern coast. Several body characters with taxonomic value in this family were reviewed under the stereo microscope and scanning electron microscope, with special emphasis on the neuropodial uncini. Remarks on these special chaetae are included in the diagnoses.